The impact of the maritime border on the development of Po- land’s border areas in terms of expenses of foreigners and the COVID-19 pandemic - Malkowska, Agnieszka; Malkowski, Arkadiusz; Tokarz-Kocik, Anna (Quaestiones Geographicae, 2023)
The aim of this paper is to present the issue of border traffic of foreigners and their expenses on the Polish maritime border. The study is based on quantitative data on border traffic and expenses of foreigners in Poland. The time of the study was 2014–2021. Thus, the impact of the coronavirus disease (COVID-19) pandemic on foreigners’ mobility and spending in Poland was additionally taken into account. For the purpose of this paper, the following study methods were adopted: reference literature analysis, secondary data analysis and comparative analysis. The paper mainly uses data from official statistics and the Border Guard. The study has shown that the Polish maritime border generates the smallest volume of border traffic, however, its share increased during the analysed period from 0.7% in 2014 to 0.8% in 2021. Nevertheless, it is foreigners crossing the maritime border who on average spend in Poland more than twice as much as foreigners crossing the Polish land border. In 2020, they spent the most on non-food goods (40%) and services (34.7%). As the study results reveal, their spending patterns and travel purposes are different from those of foreigners crossing the land border. The potential that foreign visitors bring is significant for the development of border areas in such sectors as tourism, services and trade. The analysis of the motivation of foreigners crossing the sea border makes it possible to shape the regional development policy of this particular area.